PTU-063 A Prospective Audit Of The Use Of Tacrolimus In Patients With Refractory Subacute Ulcerative Colitis In A District General Hospital. (9th June 2014) - Dhillon, AS; Harris, AW
Abstract : Introduction: Tacrolimus appears to be effective short-term treatment for patients with refractory ulcerative colitis (UC) 1 and is recommended by NICE 2 in suitable patients. We report our experience in a district general hospital out-patient setting of tacrolimus in patients with steroid refractory subacute UC whom either failed, or were intolerant to thiopurines and as an alternate to surgery. In England, Wales and Northern Ireland infliximab may no longer be used to treat patients with sub-acute UC. 3 Methods: A prospective quality and safely assurance audit was undertaken of all patients with UC treated with tacrolimus from January 2010 until January 2014. Patients not responding to or intolerant of conventional therapy met with the consultant gastroenterologist (AWH). They were offered treatment with tacrolimus, provided with written drug information or referral for surgical management. All agreed to start treatment with tacrolimus (Prograf) 0.1 mg/kg/day in 2 divided doses and were monitored according to local protocol with FBC, UandEs and serum trough levels at weeks 2, 4 and 3 monthly thereafter. The dose of tacrolimus was titrated aiming for serum trough levels between 5–20 ng/mL. Clinical response was assessed by AWH in clinic. Results: Seventeen patients (8 female; mean age 38 [range 19–86]) were treated with tacrolimus. Eleven patients (65%) had a clinical response (median treatment duration 12 [range 2–192] weeks). Four of these (45%) patients developed intolerance to tacrolimus (renal impairment n = 2; tremor n = 1; paraesthesia n = 1) and stopped treatment. Seven patients continued on tacrolimus with clinical response and without side effects. Of the 10 patients whom either failed to respond or were intolerant of tacrolimus, 7 underwent colectomy. Of the remaining 3 patients, 1 declined surgery and 2 patients have responded to treatment with methotrexate. Conclusion: Our experience supports the use of tacrolimus in patients with subacute UC refractory to conventional treatments as an alternative to elective surgery as infliximab is no longer recommended in these circumstances. 3 However only 7 of 17 (41%) patients had a clinical response and tolerated tacrolimus. Close monitoring of renal function and serum trough levels is required. The long-term efficacy and safety of tacrolimus remains unclear. References: Baumgart DC, MacDonald JK, Feagan B. Tacrolimus (FK506) for induction of remission in refractory ulcerative colitis. Cochrane Database of Systematic Reviews 2008, Issue 3. Art. No.: CD007216. DOI: 10.1002/14651858. CD007216 National Institute for Health and Care Excellence Ulcerative colitis: management in adults, children and young people CG 2013;166 National Institute for Health and Care Excellence Infliximab for subacute manifestations of ulcerative colitis TA 2008;140 Disclosure of Interest: None Declared.